2009
DOI: 10.1016/j.neuroimage.2009.02.025
|View full text |Cite
|
Sign up to set email alerts
|

White matter plasticity in the corticospinal tract of musicians: A diffusion tensor imaging study

Abstract: With the advent of diffusion tensor imaging (DTI), the study of plastic changes in white matter architecture due to long-term practice has attracted increasing interest. Professional musicians provide an ideal model for investigating white matter plasticity because of their early onset of extensive auditory and sensorimotor training. We performed fiber tractography and subsequent voxelwise analysis, region of interest (ROI) analysis, and detailed slicewise analysis of diffusion parameters in the corticospinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
206
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 252 publications
(232 citation statements)
references
References 49 publications
22
206
0
1
Order By: Relevance
“…In agreement with previous studies (Toosy et al 2003;Kraus et al 2007;Imfeld et al 2009), we found a right-greaterthan-left asymmetry of FA values in corticospinal motor tracts across all subgroups (see Fig. 2 and Tables 2 and 3).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In agreement with previous studies (Toosy et al 2003;Kraus et al 2007;Imfeld et al 2009), we found a right-greaterthan-left asymmetry of FA values in corticospinal motor tracts across all subgroups (see Fig. 2 and Tables 2 and 3).…”
Section: Discussionsupporting
confidence: 93%
“…Whereas our study complements the work of Bengtsson et al (2005) as well as that of Han et al (2009), differences have emerged between our results and those of Imfeld et al (2009) as well as those of Schmithorst and Wilke (2002), who found lower FA values in musicians relative to nonmusicians. Methodological issues might account for these differences such as the use of a subcortical ROI that included Brodmann Areas 1-4 (Imfeld et al 2009) leading to the inclusion of ascending sensory tracts, whereas our ROIs were defined to only include fiber tracts from distinct primary and nonprimary motor areas; and differences in scanning parameters may have to be considered as well. It is still unclear how diffusivity properties can be interpreted in terms of their underlying white matter structure (Beaulieu 2002;Wheeler-Kingshott and Cercignani 2009).…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations